Sustainable development of smart cities: A systematic review of the literature - Evelin Priscila Trindade; Marcus Phoebe Farias Hinnig; Eduardo Moreira da Costa; Jamile Sabatini Marques; Rogério Cid Bastos; Tan Yigitcanlar (Journal of Open Innovation: Technology, Market, and Complexity, 2017)
This paper brings together two related bodies of theory that assist understanding of processes of socio-technical system change on the global scale. These are, first, the Global Value Chain perspective (GVC) that has now mutated into Global Production Networks (GPN) and, more recently, Global Innovation Networks (GIN). Examples of why this should be are exemplified (e.g. Scandinavia's mobile telephony 'creative destruction'). The second perspective is that of Territorial Innovation Systems. This addresses the innovative core of 'creative destruction' events which, in turn, explains economic growth and development. In recent times this has been significantly undergirded by means of concepts like 'relatedness', 'proximity' and 'path dependence'. These perspectives are combined to produce a framework for analysing the contribution of an increasingly commoditised ICT assembly industry to high-value, customised 'chipset' and 'apps' design around smartphones, netbooks and flat panel display (FPD) technologies that express the GIN/TIS complex in global 'value curve' integration. Here 'creative destruction' recombinations arise because, from an evolutionary perspective, the regions in which they emerge display technological 'relatedness' and regional 'regimes' that foster co-innovation, in this case ICT-based co-innovation.
Keywords: 650; Smart city; Smart community; Sustainable city; Environmental sustainability; Sustainable urban development